Nurses' reporting of suspect adverse drug reactions: a mixed-methods study - Alessia De Angelis; Angela Giusti; Sofia Colaceci; Ercole Vellone; Rosaria Alvaro (Istituto Superiore di Sanità, 2015)
OBJECTIVE: To assess nurses' knowledge, attitudes and practices (KAP) towards spontaneous adverse drug reactions (ADRs) reporting. METHODS: The mixed-method study was conducted following a quanti-qualitative sequential approach: a survey (using a KAP questionnaire) followed by a focus group was performed. RESULTS: In the quantitative findings, responders (570 hospital nurses) declared that they were unaware of the pharmacovigilance system (58.1%, n = 331); where to find the reporting form (63.5%, n = 362); how fill it in (71.6%, n = 408); to whom and how to send it (65.8%, n = 375). Only 11.1% (n = 63) reported ADRs. The qualitative phase supported the quantitative findings and provided new information about other factors that condition ADR reporting: misinterpretation of the meaning of "reporting", unawareness of nurses' autonomy in ADR reporting and fear of consequences after ADR reporting. CONCLUSION: Nurses are not fully aware of their role in ADR reporting. We recommend educational interventions and management changes.